Numerical examination of a model rotor in brownout conditions - Kutz, Benjamin M.; Günther, Tobias; Rumpf, Andreas; Kuhn, Alexander (Annual Forum Proceedings - AHS International, 2014)
In the present study a flow simulation of a rotor hovering in ground effect was performed and compared to an experimental study from literature. Different reconstruction schemes in the finite volume flow solver were employed, leading to a computation of second and fifth order accuracy in space. The higher order computation was also performed on different grids with six and 23 million grid cells. The integral simulation values were compared to the experimental results and other literature, showing good agreement. Further on, the vortex conservation of the several schemes was compared. The higher order computation yields a much longer vortex preservation and a much better shape approximation, especially with a fine spatial resolution of the computational domain. Moreover, brownout simulations were done in a one-way coupled post processing mode of the flow computation. The results show that a good preservation of the vortices is crucial for a following brownout simulation, which leads to the necessity of a fine resolution and high order computations. The influence of the particle size was examined, leading to the finding that especially a mix of big and small particles in the sediment bed may lead to severe brownout conditions, when flying near the ground. The blade tip vortices are interacting with the sediment and are one of the main drivers of particle entrainment in brownout conditions. ©2014. All rights reserved.
CRIS-Team Scopus Importer:2020-09-23